Arsenate and cadmium content in soils of the Cerrado bioma Teores de arsênio e cádmio em solos do bioma Cerrado - Guilherme L.R.G. (2013)
Knowledge on As and Cd levels in soils is important to monitor the entry of these elements into the food chain from anthropogenic sources. The purpose of this study was to determine the natural content of As and Cd in representative soils of the Cerrado region, Brazil. Soil samples were collected from three sub-regions: G (eastern Goiás), T (Triângulo Mineiro) and N (northeastern MG). To determine the soil levels of As and Cd, samples were digested by acid attack in a microwave oven, using USEPA 3051A. The element content was quantified by graphite furnace atomic absorption spectrometry. The average As levels decreased in the following order: sub-region G (3.29 mg kg-1), sub-region T (2.18 mg kg-1) and sub-region N (0.62 mg kg-1). For Cd, the soil levels in the sub-regions G (2.45 μg kg-1) and T (1.88 μg kg-1) were equal to and higher than in N (1.16 μg kg-1). The greatest concentrations of As and Cd were found in G (Plinthosols and Inceptisols), whereas the lowest levels were found in the Neosols.